2019
DOI: 10.33640/2405-609x.1269
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic and flavonoid contents of Anacyclus pyrethrum Link plant extracts and their Antioxidant activity

Abstract: Total phenolic and flavonoid contents of Anacyclus pyrethrum Link plant extracts Total phenolic and flavonoid contents of Anacyclus pyrethrum Link plant extracts and their Antioxidant activity and their Antioxidant activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…Since it is speculated that calorimetric assays may not be able to give a complete picture of the quality and quantity of different flavonoid and phenolic components in any extract [30], we underwent HPLC technique to validate the existence of phenolic and flavonoid components in the extracts (Table 2; Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Since it is speculated that calorimetric assays may not be able to give a complete picture of the quality and quantity of different flavonoid and phenolic components in any extract [30], we underwent HPLC technique to validate the existence of phenolic and flavonoid components in the extracts (Table 2; Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, in the TAC test, that the anthocyanins extracts appear better total antioxidant capacity. This difference in the scavenging activity between the extracts could be because of the structure, quality, and functional capability of those compounds in the tested samples (Chouikh et al, 2018;Elazzouzi et al, 2019). Where; the previous researches showed that phenolic compounds with ortho-and para-dihydroxylation, a hydroxy and or a methoxy group or both have stronger antioxidant activity than simple polyphenols and also the presence of double bond conjugated and ketone groups in the whole molecule might play different polarities in the structure of the antioxidants and can be attributed to their antioxidant activity (Heshmati Afshar et al, 2012;Sroka, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The search for natural antioxidants has been the subject of several studies on A. pyrethrum ( Table 2 ) [ 6 , 8 , 39 , 45 , 46 ]. In a previous study, the author and his collaborators studied the antioxidant potency of the MeOH ext., the Aqu.…”
Section: Biological and Pharmacological Actionsmentioning
confidence: 99%
“…recorded an antioxidant effect with IC 50 of 13.41, 60.17 and 120.66 μg/mL, respectively. In addition, Elazzouzi et al [ 45 ] studied the antioxidant efficacy of the A. pyrethrum root extracts from the Timatidite region, Morocco. They reported that the MeOH ext., BuOH fra., AcEth fra.…”
Section: Biological and Pharmacological Actionsmentioning
confidence: 99%